(untitled) (International Journal of Built Environment and Sustainability, 2025)
Existing structures have significant potential to control urban growth and resource consumption. Several studies are focused on enhancing the energy efficiency of current buildings and evaluating their adaptability. Nevertheless, the main issue lies in the lack of a comprehensive method that seeks to achieve the sustainability of already constructed structures on an urban scale. In this study, the concept of “contextual sustainability” reveals the necessity of an enhancement method that suggests that the sustainability of distinctive built environments depends not only on their structural integrity but also on their social and spatial connection capacities with the existing urban texture. The aim of this research is to support the sustainable enhancement of existing buildings in the city center by using a “contextual sustainability” approach. This process included identifying both common and unique character areas and focus axes by the headings of Settlement, Street Pattern, Architectural Design, Block Layout, Building Types, Land Use, Accessibility, and Place Identity under the “contextual analysis” method. Following this, “scenario-based enhancement plans” are created for each identified character area and focus axes. In conclusion, the “contextual sustainability” method highlights that each urban area has a unique role, requiring tailored enhancement strategies. Enhancement scenarios benefit the environment and promote social, cultural, and economic growth, supporting broader urban sustainability goals. Therefore, existing buildings with different structural features and socio-cultural uses should be considered within the context of their environment before enhancement. Integrated solutions with high-scale urban goals should be determined. Enhancement approach not only envisions the integration of existing buildings into urban uses and targets also provides a practical roadmap for doing so. Tailored to each building’s environmental context, this method, which can be applied to other cities, offers a valuable guidance for urban planners and designers in diverse urban settings.